Tujuan Amerika Serikat Memberikan Bantuan Luar Negeri kepada Liberia dalam Menangani Outbreak Ebola Tahun 2013-2015 - Budiarti, Ni Made; Kumala Dewi, Putu Ratih; Widya Nugraha, A. A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2020): Jurnal Hubungan Internasional 2020, 2020)
ABSTRACT   The Ebola outbreak that happened in West Africa in 2014 was not only affected badly in Liberia, but also the health security in The United States of America (US). The US had to assemble three of its state institutions to handle the Ebola virus outspread in Liberia. The said three institutions are Central for Disease and Control Prevention (CDC), the US Agency for International Development (USAID), and Department of Defense (DoD). The purpose of the US providing foreign assistance to Liberia is to maintain the country’s cecurity from threat of communicable disease to its citizens. The conceptual frameworks that used are Foreign Aid and National Interest. This research shows that the US utilized the foreign aid offers to Liberia in order to defend the national security from threats, including the health threat. Keywords: Ebola Outbreak, Foreign Aid, National Interest, National Security ABSTRACT   The Ebola outbreak that happened in West Africa in 2014 was not only affected badly in Liberia, but also the health security in The United States of America (US). The US had to assemble three of its state institutions to handle the Ebola virus outspread in Liberia. The said three institutions are Central for Disease and Control Prevention (CDC), the US Agency for International Development (USAID), and Department of Defense (DoD). The purpose of the US providing foreign assistance to Liberia is to maintain the country’s cecurity from threat of communicable disease to its citizens. The conceptual frameworks that used are Foreign Aid and National Interest. This research shows that the US utilized the foreign aid offers to Liberia in order to defend the national security from threats, including the health threat. Keywords: Ebola Outbreak, Foreign Aid, National Interest, National Security